Gallstones. (November 2015) - Noble, Fergus; Johnson, Colin
Abstract: Gallstones are common, but most are asymptomatic and need no treatment. Typical presentations include biliary colic and acute cholecystitis. Chronic symptoms overlap with irritable bowel syndrome and non-ulcer dyspepsia, which may lead to uncertainty in identifying the cause of the symptoms. Complications of gallstones include empyema and mucocele of the gallbladder, acute pancreatitis and obstructive jaundice due to bile duct stones or Mirizzi's syndrome. The diagnosis of gallbladder stones requires ultrasonography. Duct stones can be confirmed non-invasively by magnetic resonance imaging. Symptomatic gallbladder stones are treated by laparoscopic cholecystectomy. Occasionally, empyema in an unfit patient is managed by percutaneous cholecystostomy; cholangitis usually responds to biliary drainage by endoscopic sphincterotomy with or without stenting. Stones in the bile duct can be removed by laparoscopic or open surgery, or by endoscopic sphincterotomy (ES). Obstructive jaundice is usually best treated by ES and stone extraction, or, if the stones are large or impacted, by insertion of a plastic pigtail stent. In an elderly unfit patient, this may be serially changed as long-term management, if surgical treatment is not considered appropriate.